DECISION SUPPORT SYSTEM FOR THE SELECTION OF PENCAK SILAT ATHLETES USING AHP - TOPSIS - Tulus Parmonangan; Mhd Arief Hasan; Walhidayat; Feldiansyah Nasution (Universitas Lancang Kuning, 2022)
The name Setia Hati Terate Brotherhood means prioritizing relationships between others that grow from a sincere, sincere, and clean heart. In addition, it was also explained that all members of the Setia Hati Terate Brotherhood are one brother who does not distinguish between rank, degree, and dignity as well as ethnicity, religion, race, and inter-group (SARA). One of the constraining factors for the development of Pencak silat which is in the spotlight is the lack of trainers who are qualified in selecting athletes. Considering all the reasons for the problems at the research site, it is necessary to create a decision support system that can be used by coaches and organizers of an open selection that can assist in selecting athletes to get the most potential athletes to achieve maximum performance. The selection system for Pencak silat athletes will use the AHP method which can decompose problems into a hierarchy so that it is easy to solve, while TOPSIS is a ranking method that has the advantage that it considers the best solution not only the solution closest to the ideal solution but also the most far from a negative solution. The method used is the Analytical Hierarchy Process (AHP) and Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) with the PHP programming language. This study has applied the analytical hierarchy process (AHP) method to determine and test the consistency of the weight of the criteria which includes 4 criteria, namely physical, technical, psychological, and strategic. This research uses the application of the AHP and (TOPSIS) methods with the test results, it is concluded that the system built is more effective in selecting Pencak silat athletes than the test team without using the system.